Dynamic testing of solid oxide electrolysis cells standard operating procedure - Zhikuan Zhu; William T. Gibbons; Nicholas J. Kane; Michael C. Tucker (Frontiers in Energy Research)
This study focuses on establishing a standardized dynamic operation protocol for testing Solid Oxide Electrolysis Cells (SOECs), highlighting their potential in dynamic energy applications due to their high efficiency, flexibility, and adaptability to dynamic conditions. Detailed documentation of sample preparation, selection of sealing materials, design of test equipment, testing parameters and cautions for dynamic cell testing is provided. This work aims to address gaps in the existing literature which lacks comprehensive guidance on, and discuss common pitfalls related to, dynamic testing.